63.2k views
0 votes
-6y+17=3y-10 solve this equation

2 Answers

4 votes

Answer:

The answer is Y=3

Explanation:

when you get all the varibles together and subtract from both side you'll be left with -9y+17=-10 so to get 17 to the other side you have to do the inverse operation and that would be to subtract.This means you have to subtract to both side 17-17 would cancel out and -10-17 would be -27.

Finally in order to get Y alone you once again have to do the inverse operation and the inverse of multiplying is dividing so -27/-9 would be positive 3. So Y=3

User Cat Plus Plus
by
5.1k points
7 votes

Answer:

y=3

Explanation:

Step 1: Subtract 3y from both sides.

−6y+17−3y=3y−10−3y

−9y+17=−10

Step 2: Subtract 17 from both sides.

−9y+17−17=−10−17

−9y=−27

Step 3: Divide both sides by -9.

−9y

−9

=

−27

−9

User Arturski
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.